Combination of Conventional and Innovative Methods of Teaching Healthcare Disciplines in the Training of Future Teachers - Lesіa V. Kravchenko (Mukachevo State University, 2021)
The relevance of the study is explained by the need to develop a modern system of teaching healthcare disciplines in the training of future teachers, using a combination of conventional and innovative teaching methods. In this regard, this study aims to identify the main factors influencing the quality of education of future teachers, to cover the methods of modernisation and control of curricula in healthcare disciplines, to describe the main aspects of professional teacher development, to predict and substantiate the possible consequences of conventional and innovative methods of teaching healthcare disciplines in the training of future teachers for the education system and society in general. The leading method to study this issue was the systems analysis, which can be used to investigate the combination of conventional and innovative methods of teaching healthcare disciplines in the training of future teachers. In addition, this study involved the following research methods: the method of logical analysis, comparative method, methods of synthesis and deduction, the method of classification. The study included the analysis results, identified the main factors influencing the quality of education of future teachers and methods of modernisation and control of curricula in healthcare disciplines, described the main aspects of professional and successful teacher's development, predicted, and substatiated the possible consequences of conventional and innovative methods of teaching healthcare disciplines in the training of future teachers. The results are presented in the form of tables and figures. The materials of the study are of practical value for teachers and students of pedagogical higher educational institutions, employees of the Ministry of Science and Education of Ukraine, public activists